A new method for accurately and precisely measuring flake platform area. (August 2016) - Muller, Antoine; Clarkson, Chris
Abstract: The use of 3D scanning to measure platform size is remarkably accurate and precise and has been used to estimate reduction intensity in lithic assemblages. While using 3D scans to measure lithic artefacts remains best practice in archaeology, the use of 3D scanning technology is seldom possible in real-world archaeological scenarios. Time constraints, budgetary constraints, large sample sizes, remote fieldwork locations, unreliable access to electricity and unsuitable raw material types can render 3D scanning unfeasible. In such scenarios, platform size is typically estimated by multiplying calliper measurements of platform width and thickness, forming a rectangular approximation of the platform. As few platforms resemble rectangles, we find that this method of platform measurement approximately doubles true platform size and is neither accurate nor precise. To remedy this overestimation, this paper introduces and tests the Geometric Approximations of Platforms (GAP) method, where simple 2D shapes (triangle, rhombus, trapezoid and ellipse) are employed in favour of the currently used rectangular approximations. Compared with platform width and thickness measurements, the GAP method is an equally simple and easily applied method that significantly increases both the accuracy and precision of platform measurements, being statistically indistinguishable from 3D scanned platform area values. Moreover, we offer a means by which platform width and thickness values can be converted to be used in conjunction with those obtained from the GAP method, meaning that inter-site comparisons with previously analysed assemblages would not be hindered for those employing the GAP method. Highlights: Comparisons of different platform measurement methods with highly reliable 3D scans Standard platform measurements shown to be neither accurate nor precise Introduction and test of Geometric Approximations of Platforms (GAP) method Simple 2D shapes used to approximate experimental platforms more reliably GAP method offers significant improvements in accuracy and precision.